2019
DOI: 10.13106/jafeb.2019.vol6.no4.159
|View full text |Cite
|
Sign up to set email alerts
|

Cosmopolitanism and the Mediating Effect of Country Image on Consumers’ Purchase, Visit and Investment Intentions

Abstract: The paper aims to understand the mediating effect of Country Image (CI) on the relationship between consumer cosmopolitanism and consumers' purchase, visit and investment intentions towards a foreign country, considering the moderating effects of ethnocentrism, materialism, product familiarity, and visits to a country in a global market. The study extends research on the global and local consumption by simultaneously analysing the influence of country image dimensions and several moderating effects on consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Brand image has been an attractive topic of debate in the marketing literature (Cho et al, 2010;Lee & Lim, 2020;Sousa et al, 2019). Brand image has performed a critical role in distinguishing among businesses and has played a significant role as a powerful marketing tool (H. Park & Park, 2019).…”
Section: Brand Imagementioning
confidence: 99%
“…Brand image has been an attractive topic of debate in the marketing literature (Cho et al, 2010;Lee & Lim, 2020;Sousa et al, 2019). Brand image has performed a critical role in distinguishing among businesses and has played a significant role as a powerful marketing tool (H. Park & Park, 2019).…”
Section: Brand Imagementioning
confidence: 99%
“…Attitudes toward cultural products were composed of a total of four question items. The country image consisted of five items [56,[58][59][60][61][62][63], and purchase intention consisted of three items [49][50][51][52][53]. A questionnaire was developed to collect data for this study.…”
Section: Research Methodology Data Collection Measurement Of Variablesmentioning
confidence: 99%
“…Even for familiar products, existing information or beliefs about products from a specific country are inferred from the national image, which affects consumer purchase decisions [56,58,59]. Previous studies have reported that country image is highly significant because it provides strategic information to firms that operate across borders by exporting products, manufacturing abroad, and competing in their home markets against foreign companies [60][61][62]. Country image research is becoming increasingly important and prominent because of the growing trend in free trade and intercountry exchanges [62].…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of "He who dies with the most toys win" is easily find especially in a society where materialism is promoted constantly. For people who value materialism believe that acquiring possessions is important (Sousa et al, 2019).…”
Section: Materialismmentioning
confidence: 99%